2013
DOI: 10.5812/ijhrba.10296
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life of Young Addict Women in Mashhad, IR Iran

Abstract: BackgroundQuality of life (QoL) stands for to the general well-being of the populations in the societies. Quality of life should not be confused with the concept of standard of living, which is based primarily on income. Instead, standard indicators of the QOL include not only wealth and employment, but also built environment, physical and mental health, education, recreation and leisure time and social belonging.ObjectivesThis study attempted to evaluate the QoL of the young addicted women compared to non-add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…The findings of this study supported a relationship between cultivating a more mindful way of being and a tendency to experience better HRQOL. Considering a relationship between poor HRQOL and addiction ( 6 ), the development of short-term efficient therapeutic techniques such as MBSR for increasing HRQOL is crucial. The generalization of the results of the present study was limited by the small sample; hence, future research should focus on larger and more heterogeneous samples of individuals with substance use disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of this study supported a relationship between cultivating a more mindful way of being and a tendency to experience better HRQOL. Considering a relationship between poor HRQOL and addiction ( 6 ), the development of short-term efficient therapeutic techniques such as MBSR for increasing HRQOL is crucial. The generalization of the results of the present study was limited by the small sample; hence, future research should focus on larger and more heterogeneous samples of individuals with substance use disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, HRQOL is used for evaluating daily life effects on health ( 5 ). The findings of the research by Khajedaluee et al demonstrated that drug abuse led to reduced HRQOL in all domains in comparison with control group and suggested that different aspects of HRQOL in addicted people were impaired ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Addiction in Iran is a primarily masculine phenomenon, and in the traditional Iranian culture, the father is responsible for providing for the family and meeting its needs; furthermore, adolescents are known in the community according to the names of their fathers (6, 12). Therefore, understanding paternal addiction is necessary when seeking to prevent adolescent suicide attempts and rehabilitate adolescents who have attempted suicide.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, because of this increased longevity and life expectancy, quality of life (QoL) has become an important issue in the public health sector. 3 According to the WHO Quality of Life Group, 'Quality of life is the individual's perception of their position in life in the context of the culture and the value systems in which they live in relation to their goals, expectations, standards, and concerns. It is a broad concept affected in a complex way in which the person's physical health, psychological state, level of independence, and social relationships are salient features of their environment'.…”
Section: Introductionmentioning
confidence: 99%